Zviad Gamsakhurdiia . Zviad Gamsakhurdiia . Zviad Gamsaxurdia . Звиад Гамсахурдия - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program discussing the mass media's notification about the death of the former President of Georgia, Zviad Gamsakhurdia. Featured in the program: Novodvorskaia, Valeriia Il'inichna (Human Rights Activist) Contributors: Svanidze, Nikolai (Anchor) В программе обсуждается сообщение средств массовой информации о смерти бывшего президента Грузии Звиаде Гамсахурдия. В программе участвуют: Новодворская, Валерия Ильинична (Правозащитница) Создатели: Сванидзе, Николай (Ведущий/Ведущая)